3D CFD simulations of air-water interaction in T-junction pipes of urban stormwater drainage system. Issue 1 (2nd January 2022) - Fang, Haoyu; Zhou, Ling; Cao, Yun; Cai, Fulin; Liu, Deyou
ABSTRACT: A 3D computational fluid dynamics model based on a volume of fluid (VOF) approach is presented to simulate air-water interactions and transient pressures in T-junction pipes of urban stormwater drainage system. The effective heat transfer due to compressible air pocket, and various k-ε and k-ω turbulence models, are considered to account for the potential energy attenuation during air-water interactions. One effective meshing method considers the boundary layer of the pipe wall and the effect of grid density. The proposed approach with RNG model can accurately reproduce the experimental pressure oscillations, including the pressure peaks and periods and the pressure damping, and is importantly helpful to explore the complicated flow characteristics. Rapid filling of T-junction pipe with trapped air undergoes: (a) with the air movement and expulsion in vertical pipe, but without any geyser; or (b) involving the air movement and expulsion in vertical pipe, accompanying the violent geyser.